THE ROLE OF EUROREGIONS IN INTEGRATION PROCESSES - Viktor Tsekhanovych (Izdevnieciba "Baltija Publishing", 2021)
Modern international relations are characterized by integration processes, among which Euroregional cooperation plays an important role. Euroregional cooperation as an element of state policy today occupies a rather important place both in the system of priorities of socio-economic development and in the direction of European integration of Ukraine. Such a policy, on the one hand, is aimed at ensuring the comprehensive development of the regions, and on the other hand, at preserving the territorial integrity of the state. It is implemented on the basis of jointly developed programs of trade, economic, scientific, technical and cultural cooperation. Active regional development is considered as one of the elements of the pan-European system of priorities, which corresponds to the fundamental integration of states through the integration of Regions. Such activities involve accelerating the socio-economic development of euroregions, personnel and infrastructure training of Regions and the country as a whole to deepen cooperation with the EU, and accelerating European integration processes. Euroregions allow their participants to quickly solve common problems, create flexible, joint economic structures, establish cross-border trade, tourism, and expand cooperation in cultural, social, environmental and other fields. Their functioning is based on the principles of local self-government and cross-border cooperation. The activation of Euroregional ties in the context of integration and the creation of various forms of cooperation have positive results for the regions and for Ukraine as a whole. This makes it possible to modernize economic processes, attract foreign investment and new technologies, and create new jobs, which will lead to competition between products and the region. The integration processes that have recently been observed in Euroregions, in addition to traditional cross-border cooperation, can be distinguished as innovative, which include Euro-regional and cross-border clusters, business incubators, technology parks. All this leads to increased competitiveness of the regions, which leads to increased effective use of the region's potential.